2020
DOI: 10.1101/2020.07.17.209437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid tolerance to morphine in the myenteric neurons of the small intestine is independent of β-arrestin-2 and mediated by PKC

Abstract: The differential rates of opioid tolerances raise the question of discrete underlying mechanisms. While opioid tolerance is strongly linked to the development of dependence, there is a dissociation between the two phenomena in the gut as tolerance does not develop to chronic opioid-induced constipation, but diarrhea still manifests upon withdrawal. Here, we find that tolerance develops to inhibition of small intestinal motility after one day of morphine exposure, and is more rapid compared to spinally-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…We investigated whether β-arrestin-2 modulates the development of chronic or “long-term” antinociceptive tolerance in mice. To induce tolerance, male and female mice were implanted subcutaneously with 50 mg or 25 mg morphine pellets, respectively, in accordance with a previous report by our laboratory (Muchhala et al, 2020). We determined the development of tolerance over 7 days by an acute challenge of morphine (10 mg/kg morphine s.c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether β-arrestin-2 modulates the development of chronic or “long-term” antinociceptive tolerance in mice. To induce tolerance, male and female mice were implanted subcutaneously with 50 mg or 25 mg morphine pellets, respectively, in accordance with a previous report by our laboratory (Muchhala et al, 2020). We determined the development of tolerance over 7 days by an acute challenge of morphine (10 mg/kg morphine s.c).…”
Section: Resultsmentioning
confidence: 99%
“…Where indicated, one or two 25 mg morphine pellets were implanted subcutaneously in the dorsum of female or male β-arrestin-2 mice for 7 days, respectively. This dose was based on a previous study, where we demonstrated that a 7-day exposure to one 25 mg and two 25 mg morphine pellets in female and male β-arrestin-2 mice, respectively, substantially right-shifted the morphine dose response curve compared to wild-type mice in the warm-water tail-withdrawal assay, indicating antinociceptive tolerance (Muchhala et al, 2020). The dose of two 25 mg morphine pellets is henceforth denoted as “50 mg” in the present study.…”
Section: Methodsmentioning
confidence: 99%